An integrative analysis of sibling influences on adult children's care-giving for parents. Issue 3 (1st March 2021) - Vergauwen, Jorik; Mortelmans, Dimitri
Abstract: The extent to which, and the reasons why, children help to care for their parents are examined in an extensive range of literature. Although care for parents essentially takes place in parent–child dyads, many of these studies acknowledge that the amount of care a child gives is generally the outcome of collective decisions in multiple-child families. However, to our knowledge, no research in Europe enhances our understanding of how sibling characteristics influence an individual child's care-giving. Using data for 14 European countries from the Survey of Health, Ageing and Retirement in Europe, the present study relates pre-care-giving sibling characteristics to children's subsequent start of giving care. This longitudinal approach allows correction for the endogenous nature of time-changing predictors. The analysis demonstrates that daughters start to care more often when they have brothers instead of sisters. This pattern of gendered intergenerational care particularly applies to southern European countries. We also observe that both pre-care-giving parent–sibling frequency of contact and geographic distances predict children's care-giving transition strongly. Children who are closer to their parents than siblings in terms of contact and proximity have higher odds of care-taking. Finally, being the only child without a job enhances the start of care-giving as well. The results suggest that sibling characteristics are an important factor in explaining intergenerational care differences between children in Europe.